Peningkatan Disolusi Tablet Tadalafil Dengan Metode Kompleks Inklusi Betasiklodekstrin dan Variasi Eksipien Penghancur. - Rachmawan, Rifky Fitrah; Setianto , Arif Budi; Wahyuningsih , Iis (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Tadalafil (TDL) is a drug clinically proven to treat erectile dysfunction, benign prostatic hyperplasia, and pulmonary hypertension. TDL is classified as a BCS Class II drug, which means it has high permeability but low solubility. Solubility enhancement is achieved through the inclusion complex method and verified by dissolution testing. This study aims to determine the dissolution profile of tadalafil inclusion complex tablets using the β-cyclodextrin (βCD) inclusion complex method with disintegrant variations. The results show that the tablet hardness is: R1 = 6.6 ± 0.5 kgf, R2 = 6.48 ± 1.4 kgf, and R3 = 6.6 ± 1.3 kgf. The disintegration time evaluation shows: R1 = 4.66 ± 1.08 minutes, R2 = 5.08 ± 0.91 minutes, and R3 = 5.1 ± 1.1 minutes. Each formulation's tensile strength test results are: R1 = 1.3 MPa, R2 = 1.3 MPa, and R3 = 1.1 MPa. The average drug content in the inclusion complex tablets is: R1 = 104.11 ± 1%, R2 = 106.23 ± 0.1%, and R3 = 105.09 ± 1.9%. The dissolution profile of the inclusion complex tablets at the 30-minute mark is: R1 = 85.2 ± 4.2%, R2 = 79.7 ± 3.6%, and R3 = 77.4 ± 5.3%. Variations in disintegrants significantly affect the dissolution profile during the early minutes, which impacts the overall dissolution profile. The TDL-βCD inclusion complex method successfully achieved the Q value by the monograph specifications.